The IMPLEMENTATION OF TRACKING SYSTEM IN THE REAL TIME OF ANDROID FOR SENDING PERSONEL COORDINATION BASED ON MQTT. - Faesol, Agus; Ashar, Imam; Yulisusianto, Gatut (Jurnal Telkommil, 2021)
Abstract: In the world of technology that is increasing, then as humans we will not be separated from the process improvement that occurs. From year to year, it is certain that this increase will certainly. Increasingly rapidly occurring in communication technology. Communication technology has also penetrated the military world, especially in MQTT-based communications. In this research, MQTT-based technology is applied to implement real time tracking system on android. This system is used to send the longitude and latitude coordinates of the personnel so that these points can be known directly via android. From this pure experimental research method, the coordinate point data will continue to be monitored and the existence can be known continuously. This system is designed on a VPS server or Virtual Private Server, so that all devices even though none of the networks can communicate with each other as long as they have access rights for application user.